2020
DOI: 10.1101/2020.04.04.024943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D cell culture models demonstrate a role for FGF and WNT signaling in regulation of lung epithelial cell fate and morphogenesis

Abstract: 15FGF signaling plays an essential role in lung development, homeostasis, and regeneration. Several 16 FGF ligands were detected in the developing lungs, however, their roles have not been fully elucidated. 17 We employed mouse 3D cell culture models and imaging to ex vivo study of a) the role of FGF ligands 18 in lung epithelial morphogenesis and b) the interplay of FGF signaling with epithelial growth factor 19 (EGF) and WNT signaling pathways. In non-adherent conditions, FGF signaling promoted formation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…We observed that two mesenchymal cell clusters identified by scRNA-seq are enriched for expression of the WNT agonist RSPO2 throughout the developmental time frame analyzed, and spatial localization showed that RSPO2 is expressed adjacent to the bud tip domain. It is known that high WNT signaling conditions are necessary for the maintenance of the bud tip progenitor cell state in vitro Miller et al, 2018;Rabata et al, 2020), which made this cell population a strong bud tip-associated mesenchymal cell candidate.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that two mesenchymal cell clusters identified by scRNA-seq are enriched for expression of the WNT agonist RSPO2 throughout the developmental time frame analyzed, and spatial localization showed that RSPO2 is expressed adjacent to the bud tip domain. It is known that high WNT signaling conditions are necessary for the maintenance of the bud tip progenitor cell state in vitro Miller et al, 2018;Rabata et al, 2020), which made this cell population a strong bud tip-associated mesenchymal cell candidate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this observation, there is an opportunity to further refine the signaling pathways that are manipulated to expand and maintain NKX2-1 + lung lineages; however, this may prove challenging given the redundant use of some pathways (i.e. WNT) to maintain stem/progenitor cells from both lineages (Pinto and Clevers, 2005; Kapoor, Li and Leiter, 2007; Volckaert and De Langhe, 2015; Chin et al ., 2016; Nikolić and Rawlins, 2017; Yan et al ., 2017; Miller et al ., 2018; Rabata et al ., 2020; Aros, Pantoja and Gomperts, 2021). We observed that hindgut lineages expand after passaging organoids using the standard approach of mechanically shearing them into small fragments.…”
Section: Discussionmentioning
confidence: 99%